Mechanical Properties of Phenolic Composites Reinforced with Flax-g-copolymers Prepared under Different Reaction Conditions - A Comparative Study - Susheel Kalia; B. S. Kaith (E-Journal of Chemistry)
Graft copolymers of methyl methacrylate (MMA) and its binary mixtures such as MMA + ethyl acrylate (EA), MMA + acrylonitrile (AN), MMA + acrylic acid (AA), MMA + vinyl acetate (VA), MMA + acrylamide (AAm) and MMA + styrene (Sty) with flax fiber have been prepared in air (IA) and under the influence of microwave radiations (MWR). Synthesized flax-g-copolymers under two different reaction conditions were used as reinforcing material in the preparation of phenol-formaldehyde composites. Mechanical properties such as wear resistance, modulus of rupture (MOR), modulus of elasticity (MOE) and stress at the limit of proportionality (SP) were measured and a comparative studied has been made. It has been found that composites reinforced with flax-g-copolymers-MWR showed better mechanical properties in comparison to composites reinforced with flax-g-copolymers-IA